Effect of Pore Size on the Gasification of Biomass Char. (August 2015) - Fatehi, Hesameddin; Bai, Xue-Song
Abstract: The evolution of char porous structure can affect the gasification rate of biomass char. A model based on the classical capillary pores is developed taking into account different conversion rates for pores having different radii. The contribution of different pores with different radii is taken into account using an effectiveness factor presented for each pore radius. As the char conversion proceeds, the pore enlargement increases the contribution of micro-pores; consequently the effective surface area will increase. The increase in the effective surface area leads to an increasing reactivity of char during the entire conversion process. This model is used to examine the contribution of each group of pores in the conversion of biomass char and can be a useful tool for developing and calibrating intrinsic kinetic rates from experimental data.